2016
DOI: 10.1016/j.jad.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Insight in bipolar mania: evaluation of its heterogeneity and correlation with clinical symptoms

Abstract: Results suggest that patients with BD are reasonably capable of identifying that their condition implies consequences but have more impaired awareness of their energy and activity levels. A lower level of insight specifically about symptoms correlates with more severe symptoms of agitation/energy, which suggests a psychomotor nucleus able to impair insight in mania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
(25 reference statements)
0
12
2
1
Order By: Relevance
“…6,20 To the best of our knowledge, no other study has evaluated the correlation between insight and depressive symptoms. It is worth noting that the correlations found in the current study (bipolar depression) were generally weaker than those reported for bipolar mania, 8 which may reflect a more limited contribution of symptoms to loss of insight in bipolar depression or a reduced variance of insight into this condition.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…6,20 To the best of our knowledge, no other study has evaluated the correlation between insight and depressive symptoms. It is worth noting that the correlations found in the current study (bipolar depression) were generally weaker than those reported for bipolar mania, 8 which may reflect a more limited contribution of symptoms to loss of insight in bipolar depression or a reduced variance of insight into this condition.…”
Section: Discussioncontrasting
confidence: 81%
“…8 In contrast with bipolar mania, the current study found that insight in bipolar depression did not fluctuate according to the object. 8 It is possible that insight in bipolar depression is influenced by a general factor, such as a negative bias in appraisal of self-ability that does not change with different objects.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Previous studies exploring the relationship between specific neuropsychological abilities and medical decision-making showed that tests evaluating executive functioning correlated with the reasoning component of treatment consent capacity in clinical and healthy populations (for review, see Palmer and Savla, 2007). Additionally, mania has been associated with reduced awareness about the condition (de Assis da Silva et al, 2015a,b; 2016), including in patients with AD (Migliorelli et al, 1995). Lack of awareness about the condition may impact negatively reasoning about the treatment.…”
Section: Discussionmentioning
confidence: 99%